Angiogenesis-Based Dermatology - Arbiser, Jack L. (Springer London : Imprint: Springer, 2017)
This book covers in detail all aspects of angiogenesis in dermatology. Angiogenesis is a principle that can be used to guide treatment of diseases of any organ system. Dermatologists already inhibit angiogenesis as part of their treatment of multiple common dermatologic disorders, including acne, warts, and nonmelanoma skin cancer. Angiogenesis-Based Dermatology encompasses information and knowledge from a diverse background of related topics to enable readers to have a full understanding of the subject in order to optimally manage patients with this group of diagnoses. It provides a guide to the principles of angiogenesis that will allow all involved in dermatology from the medical student and nurse practitioner to the experienced dermatologist to apply these principles for the treatment of patients.- Resumé vydavatel
Keywords: dermatologie; kožní nemoci; dermatology; skin diseases; elektronické knihy; sborníky; electronic books; papers of several authors